THE EFFECTS OF FACILITIES, INFORMATION SYSTEMS, AND INTEGRITY ON SERVICE SATISFACTION, WITH SERVICE QUALITY AS AN INTERVENING VARIABLE, AT THE BPS – STATISTICS BATAM MUNICIPALITY - Debora Sinaga; Ngaliman; Mohamad Gita Indrawan (CV. Radja Publika, 2026)
High-quality public services are a key factor in ensuring user satisfaction. As a provider of statistical services, the Batam City Central Statistics Agency (BPS) is required to deliver services that are fast, convenient, accurate, and conducted with integrity to meet the needs of statistical data users. However, user satisfaction with these services is influenced by various factors, including facilities, information systems, integrity, and service quality. This study aims to analyze the influence of facilities, information systems, and integrity on service satisfaction, with service quality as an intervening variable at the Batam City BPS.This study employs a quantitative approach using a survey method. The study population consists of all users of statistical data services at the Batam City BPS, including those who receive services in person and those who access services through the official Batam City BPS website. The sampling technique used purposive sampling with a sample size of 100 respondents. Data were collected through the distribution of questionnaires using a five-point Likert scale and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS 4 software.The results of the study indicate that facilities do not have a significant effect on service satisfaction or service quality. The information system does not have a significant direct effect on service satisfaction but has a positive and significant effect on service quality. Integrity has a positive and significant effect on both service satisfaction and service quality. Additionally, service quality has a positive and significant effect on service satisfaction. The results of the indirect effect tests indicate that facilities do not have a significant effect on service satisfaction through service quality. The information system has a significant effect on service satisfaction through service quality. Integrity has a significant effect on service satisfaction through service quality.This study concludes that user satisfaction with services at the Batam City BPS is more strongly influenced by service quality, which is supported by the integrity of civil servants and an effective information system. Therefore, efforts to improve service satisfaction should focus on strengthening the integrity of